ADOPTION BEHAVIOUR OF GROUNDNUT FARMERS IN CHITTOOR DISTRICT OF ANDHRA PRADESH - P. BALAHUSSAIN REDDY (The Journal of Research ANGRAU, 2023)
Adoption behaviour of 180 farmer beneficiaries from eight adopted villages of RAAS Krishi Vigyan Kendra (KVK), Chittoor with respect to the recommended Groundnut production technologies was studied duing the year 2012.Four types of behaviour viz., full adoption, partial adoption, discontinuation and non-adoption for fourteen recommended package of practices in Groundnut was analysed.The results revealed that overall there was a positive trend (greater than 50% full adoption for ten recommended practices) in the adoption behaviour of the beneficiaries of KVK. However, KVKs need to put efforts to influence the farmers (through different interventions) for complete adoption of the recommended technologies for improving the productivity and profits of the farmers.